1997
DOI: 10.1161/01.res.80.6.772
|View full text |Cite
|
Sign up to set email alerts
|

Outward K + Current Densities and Kv1.5 Expression Are Reduced in Chronic Human Atrial Fibrillation

Abstract: Chronic atrial fibrillation is associated with a shortening of the atrial action potential duration and atrial refractory period. To test the hypothesis that these changes are mediated by changes in the density of specific atrial K+ currents, we compared the density of K+ currents in left and right atrial myocytes and the density of delayed rectifier K+ channel alpha-subunit proteins (Kv1.5 and Kv2.1) in left and right atrial appendages from patients (n = 28) in normal sinus rhythm with those from patients (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
369
3
5

Year Published

1998
1998
2009
2009

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 506 publications
(405 citation statements)
references
References 25 publications
28
369
3
5
Order By: Relevance
“…In some cases, more significant rate adaptation can be observed at the shortest CLs (Kim et al, 2002;Dobrev and Ravens, 2003). Similar alterations to those given by Courtemanche et al (1999) have been observed in other experiments as well (Dobrev and Ravens, 2003), including substantial reductions in I Ca,L (Bosch et al, 1999;Van Wagoner et al, 1999;Skasa et al, 2001;Workman et al, 2001) and I to (Van Wagoner et al, 1997;Bosch et al, 1999;Brandt et al, 2000;Grammer et al, 2000;Workman et al, 2001). The reduction in I Kur proposed by Courtemanche et al (1999) has been found in some studies (Van Wagoner et al, 1997;Brandt et al, 2000) but not in others (Grammer et al, 2000;Workman et al, 2001).…”
Section: Atrial Fibrillation-induced Changes In Rate Dependence and Msupporting
confidence: 83%
“…In some cases, more significant rate adaptation can be observed at the shortest CLs (Kim et al, 2002;Dobrev and Ravens, 2003). Similar alterations to those given by Courtemanche et al (1999) have been observed in other experiments as well (Dobrev and Ravens, 2003), including substantial reductions in I Ca,L (Bosch et al, 1999;Van Wagoner et al, 1999;Skasa et al, 2001;Workman et al, 2001) and I to (Van Wagoner et al, 1997;Bosch et al, 1999;Brandt et al, 2000;Grammer et al, 2000;Workman et al, 2001). The reduction in I Kur proposed by Courtemanche et al (1999) has been found in some studies (Van Wagoner et al, 1997;Brandt et al, 2000) but not in others (Grammer et al, 2000;Workman et al, 2001).…”
Section: Atrial Fibrillation-induced Changes In Rate Dependence and Msupporting
confidence: 83%
“…31 Specifically functioning in the atria, I kur, is a crucial determinant for phase I repolarization during action potentials. 32,33 The strong evidence that KCNA5 expresses much more extensively in human atria than in ventricles, and that I Kur has not been recorded in the human ventricle, 32,34 implicates Kv1.5 as a potential selective target for the medical management of AF. 35 Importantly, it should be noted that traditional therapeutics for AF are based on inhibition of I Kur , 31 and would not be applicable in patients with loss of function of Kv1.5.…”
Section: Kcna5 Mutations and Atrial Fibrillation Y Yang Et Almentioning
confidence: 99%
“…One may tentatively speculate that circulating anti-VGKC autoantibodies, which were present in 14% of our cohort and are known to impair K V 1 channel function, may contribute to chagasic oesophageal and heart disease by impairing K V 1.5 channel function. In support of this hypothesis is the fact that down-regulation of expression of this channel has been found to be associated with arrhythmia (Van Wagoner et al 1997;Lai et al 1999;Brundel et al 2001) which is a common feature of chagasic heart disease (Elizari 2002). Due to their function of regulating cellular excitability, impairment of K V 1.5 oesophageal smooth muscle would be expected to interfere with oesophageal contractility, and this may be relevant to the loss of normal peristalsis and failure of smooth muscle relaxation characteristic of oesophageal achalasia.…”
Section: Significance and Interpretationsmentioning
confidence: 98%